PLURALISME DAN MULTIKULTURALISME DALAM PENDIDIKAN ISLAM DI INDONESIA - Qomarudin, A. (TA'LIMUNA: Jurnal Pendidikan Islam, 2014)
The fundamental principle of Islam that is closely linked to the role of Islamic education to face the challenges of pluralism and multiculturalism is that Islam is a universal religion, that teaches to negate the coercion in religion. Islam, a doctrine that is widely open to being proven its truth. Islam affirms the natural diversity of human life. Islam has also a history that is very clearly associated with the compound life. Relate to the Islamic education in Indonesia that basically refers to the values of pluralism in the Qur'an and Hadith, this article offers an alternative learning that can be done in Islamic education.